Virtual Tour: Exploration of Perceptions and Acceptance by The Communities - Nugraheni, Agusta Ika; Putri, Lana; Nugraha, Bima Setya (Jurnal Pariwisata Terapan, 2022)
The Covid-19 pandemic that hit the world and Indonesia in 2019 had a significant impact on almost all industrial sectors. The Covid-19 pandemic forced every government from various countries to issued travel warnings, namely an appeal and a travel ban, to prevent the virus's faster and wider spread. In fact, the government issued flight cancellations from and out of the country. Restrictions on mobility at home and abroad significantly affect the tourism industry, related to the number of visits to various tourist destinations in Indonesia. Virtual reality (VR) technology in the tourism industry has emerged since the 2009s, its role is still limited as tourism promotion tools. The current condition of the Covid-19 pandemic is forcing tourism actors to rearrange strategies for using VR technology so that they can temporarily substitute and meet the needs of the community in traveling through virtual tourism. Studies related to public perception and acceptance of alternative travel through this technology have not been widely carried out. This study aims to explore the development of virtual tourism by analyzing the perception and acceptance of the Indonesian people towards virtual tourism. The research method used is the descriptive quantitative method. The data collection using a questionnaire that refers to product concept testing. This study indicates that most respondents know about virtual tours, but most have never taken virtual tours and are interested in taking virtual tours and are willing to pay. In addition, most respondents consider that virtual tourism can replace physical tourism.